Avaliação externa da alfabetização de jovens, adultos e idosos: um estudo no contexto do Proaja-PI - Luzmara Gonçalves de Souza (2023)
In this work, we propose to discuss the specificities of a standardized literacy assessment, with a focus on external monitoring, within the scope of a Literacy Program for young people, adults and the elderly, developed in the state of Piauí, the PROAJA, between the years of 2021 and 2022. This is a descriptive-analytical case study, in which we seek to contextualize PROAJA using both public domain documents, such as laws and regulations, and documents produced specifically for monitoring this program, such as the theoretical foundation of literacy profiles, application manuals, lives aimed at training test applicators, among others. There was also a narrative emphasis interview with an experienced manager who participated as a PROAJA consultant. When discussing PROAJA and the evaluations developed for this program, we sought to apprehend the contributions present in the literature on literacy evaluation outside the school, in the last two decades. We also seek to address PROAJA's singularities and convergences in relation to large adult literacy programs, developed in the country at the national level. The descriptions and analyzes presented lead us to the understanding that there is still a long way to go in proposing adult literacy programs, especially regarding the workload to be offered, so that this creates conditions for students to have the time necessary to effectively become literate and not just “participate” in the program. Alongside this, the very presentation of the Pedagogical Matrix of the evaluation already indicates the importance of literacy practices to contemplate the necessary skills for the appropriation of the written word by the students, which requires a continuous formation of the literacy teachers. It is necessary to consider, as we explained in different moments of this work, that the evaluation does not correspond to the uses that are made of it. A standardized assessment, focusing on skills necessary for literacy, when pedagogically appropriate, such as the one discussed here, can be appropriated in different ways by different policy executors. This factor shows that, in relation to the issue of external evaluation, there is still a long way to go, since, not infrequently, we still confuse the evaluation itself, with the uses that are made of it. Such uses, although often well-intentioned, by focusing on accountability, end up making the pedagogical use of this type of assessment secondary or even unfeasible.